University Curricula and Student Movement in Indonesia: “Gejayan Memanggil” Protest in Yogyakarta - Amalinda Savirani (Journal of Governance, 2023)
Student movements have played a significant political role in many countries in Asia, including Indonesia. They have been labeled "agents of change", and their movements are regarded as "moral forces" that push political change through street protests. Why do students join protests? What motivates them? How do their motivations relate to institutional aspects of universities, including the course materials they learn in class? This article attempts to answer these questions within an Indonesian context using the case of "Gejayan Memanggil" ('Gejayan Calling'), a 2019 student movement that had been the largest such movement in Yogyakarta since 1998. This article argues that students' self-perception as "agents of change", rather than institutional support, was their primary motivation to join the protests. Other contributing factors were the demands and form of the protest.